Immune response towards lipid peroxidation products as a predictor of progression of non-alcoholic fatty liver disease to advanced fibrosis - Albano, E; Mottaran, E; Vidali, M; Reale, E; Saksena, S; Occhino, G; Burt, A D; Day, C P (Gut, 2005)
Aims: Factors responsible for the progression of non-alcoholic fatty liver disease (NAFLD) to more severe liver injury are poorly understood. In the present study, we investigated the association between immune reactions triggered by oxidative stress and stage of NAFLD. Methods: Titres of IgG against human serum albumin adducted with malondialdehyde (MDA-HSA) or arachidonic acid hydroperoxide (AAHP) and against oxidised cardiolipin (Ox-CL) were measured in 167 NAFLD patients with steatosis only (n = 79), steatohepatitis (n = 74), or steatosis plus cirrhosis (n = 14), and in 59 age and sex matched controls. Results: Circulating IgG against lipid peroxidation products was significantly higher (p<0.001) in NAFLD patients than in controls. Oxidative stress dependent immune responses were not associated with obesity, type 2 diabetes, or with serum cholesterol, ferritin, or aminotransferase levels. Titres of lipid peroxidation related antibodies were also independent of the extent of steatosis and were similarly distributed in patients with and without necroinflammation. In contrast, the same antibodies were significantly increased in patients with advanced fibrosis or cirrhosis. Logistic regression analysis confirmed that anti-MDA antibodies were independently associated with progression of NALFD and that NAFLD patients with titres of anti-MDA-HSA antibodies above the control threshold value had a threefold (relative risk 2.82 (95% confidence interval 1.35–5.90); p = 0.007) higher risk of having advanced fibrosis/cirrhosis than patients whose antibody titres were within the control range. Conclusions: These results indicate that the presence of immune reactions triggered by oxidative stress can be an independent predictor of progression of NAFLD to advanced fibrosis.